Metode Bayes Untuk Diagnosa Penyakit Alergi Pada Anak Berbasis Web - Imam Dody Susanto; Bakhtiar Rifai; Herman Kuswanto (JURNAL TEKNIK KOMPUTER AMIK BSI, 2016)
An expert system is one of the branches of artificial intelligence technology that combines the knowledge of an expert with data searches to solve problems that are usually   done   by   an expert.  With   more   advanced   developments   in   information technology now allows people to access information from anywhere and at any time, including in the field of health. One of these allergic diseases in children, allergies are the result of the body's response to   foreign particles that enter the body.  The inability of the body to the particles that   enter the body makes a person suffers from allergies, while the symptoms caused by a different body. In this application method used is the Bayes method in which patients choose your symptoms   will then get a conclusion in the form of provisional diagnosis of the illness.  The end result of   this application is an application that will display the diagnosis of the illness based on symptoms chosen by the patient.  Keywords: Allergy Kids, Web-based, Bayes Method